The potential to exploit use of building-integrated photovoltaics in countries of the Gulf Cooperation Council - Taleb, H.M. (2009)
The use of renewable forms of energy is important throughout the world, not just in countries where there are concerns over the availability of fossil fuels. In order to develop and promote suitable energy policies for the future it is necessary to gain an understanding of stakeholder views in all countries, including those with substantial fossil fuel reserves. The volume of construction work in the Gulf Cooperation Council (GCC) countries has recently been at unprecedented levels, with a huge environmental impact from construction and also from potential future energy demands. The aim of this paper is to assess the potential to exploit use of a particular, but valuable, renewable energy option: building-integrated photovoltaics (BIPV) in those countries. Such exploitation could offset, at least in some part, the future environmental burdens. A large-scale survey, followed by a number of in-depth interviews, has been undertaken in order to examine the use of BIPV. Empirical research findings are presented, and then analysed in order to determine the current viability of a large-scale expansion of BIPV in the GCC region. The research indicates that the main factors hindering expansion are high costs and the negative public perception of BIPV in the countries concerned. Proposals are therefore provided to assist the development of suitable policies and the wider introduction of viable BIPV in the GCC markets.